An attempt in character design free of sexism and stereotypes - Pourgouris, George (Τμήμα Πολυμέσων και Γραφικών Τεχνών, Σχολή εφαρμοσμένων Τεχνων και Επικοινωνίας,Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
Video games have become a huge and important part in the lives of many people, they evolved from a simple form of entertainment into art and even education. And so their influence on children, teens and adults is quite big. And for that reason video games must pass on the right messages to the community, because they have the power to influence the way the player sees reality. The media in its many forms is filled with stereotypes, and video games are no exception. Video game characters are essential to a game, it is through these characters that the player interacts with the game, they are the physical manifestation of the player inside the virtual world of the game. And the stereotypes that affect video games mainly affect video game characters, more specifically sexist stereotypes. To clarify, women are mostly depicted sexualized, with as much as little clothing as possible and suggestive possess, not only that, their bodies are also over sexualized, with big breasts and thin waist lines. While men on the other hand, are always depicted as these powerful muscular figures with intimidating poses. This thesis will act as the “design” part of another thesis, the purpose of the previous thesis was to research and prove the existence of stereotypes in video games, while the purpose of this thesis is to design characters based on the guidelines set by the previous one. Also, research needs to be done on how to design characters and find good character designs from existing games and use them as guidelines. After the researching part is done, the designing of the characters will commence and when sufficient characters are created they will then be presented to experts to evaluate them, thus pointing out flaws that need correcting.
Keywords: Sexism; Stereotypes; Video Games; Character Design